Effect of advanced-platelet rich-fibrin combined with rosuvastatin application after open flap debridement of infrabony pocket - Tissa Rahadianti; Dahlia Herawati; Kwartarini Murdiastuti (Majalah Kedokteran Gigi Indonesia, 2022)
Open flap debridement (OFD) is an invasive therapy for chronic periodontitis with pocket 5 mm or more. However, it is difficult to achieve regeneration and new attachment with this therapy. Periodontitis starts to add growth factors and local drugs delivery as host modulation therapy. Advanced-PRF (A-PRF) contains more growth factor than PRF which plays a role in promoting fibroblast proliferation, reepithelization, extracellular matrix production, and endothelial cell migration. 1.2% rosuvastatin gel (RSV) is a local delivery drug with a pleiotropic effect that can modify host response to promoting BMSCs, BMP-2, OPG, ALP, RANKL, and osteoblasts. This study aimed to examine the effect of the application of A-PRF+RSV in OFD therapy of which the parameters were probing depth (PD), relative attachment loss (RAL), and alveolar bone height. The study samples consisted of 24 periodontal pockets which were divided into 2 groups of 12 pockets each, namely A-PRF+RSV for group 1 and PRF+RSV for group 2. Clinical evaluations were carried out on baseline, day-30, and day-90 for PD and RAL, and on baseline and day -90 for alveolar bone height. Data of PD and RAL reduction were analyzed with non-parametric test Mann-Withney, while data of reduction of alveolar bone height were analyzed with parametric Independent-T test. Group 1 obtained a statistically more significant result in reducing PD, RAL, and alveolar bone height compared to group 2 (p<0.05) To conclude, the application of A-PRF and 1.2% rosuvastatin gel in OFD procedure promotes a higher PD and RAL reduction and alveolar bone height increase than the application of PRF coupled with 1.2% rosuvastatin gel.